La ley orgánica de defensa del consumidor y la falta de facultades legales sancionadoras de la defensoría del pueblo - Manobanda Z., Ángel Bolívar (2016)
This paper Legal Research called "ORGANIC CONSUMER PROTECTION ACT AND THE LACK OF LEGAL AUTHORITY punitive THE OMBUDSMAN" addresses legal issues indisputable importance in the legal and social environment, especially the lack of information that the consumer or the user, are citizens with many cases which know their rights, hardly known a few basic rights, but do not know the right to good living, right to health, right to food, right to register their name and surnames, right to paid at overtime, holiday work, among others. Ecuadorian citizens are permanent victims of all kinds of abuse from public and private companies, which is why we have reformed the Organic Law of the consumer with the benefit of the rights of individual consumers, in order for those individuals not do more of their own, creating efficient and effective mechanisms for authorities to enforce those who do not comply with the Act. In the theoretical framework, in the nineteenth century, the abuses of power by public administration and to the demands of the majority of citizens arises, gaining strength in the various countries of Europe after World War II in America PTO whose main objective is to defend the human rights of the needy even regardless of nationality, sex, religion or race. The injustices committed with the weakest, is no coincidence, as we see is the result of a struggle for centuries before and after Christ, but economic power has always been opposed to the conquests of changes in benefit of society. Currently, the Ombudsman is an institution who legally represents us, defending our rights, and against privatization, bank holidays, attacks on human rights, among others. Since social organizations, the indigenous movement, fought for decades to achieve beneficial change, as the fifth power, the Transparency and Social Control, new function of the Ecuadorian State has the task of monitoring and control entities in the sector natural and legal public and private sector which operates in the public interest people. Ecuador as a State Constitutional Rights and Justice, in which the protection of rights is the cornerstone on which rests the current legal system, ie in our country if the Protection of rights, but instead Sites as Venezuela, Costa Rica and Peru, have institutions ombudsman's office but they know little or nothing of the complaints or claims regarding the defense of human rights, consumers and users are most vulnerable countries. The research was done using methods and procedures, using survey and interview as research methods leading to the observation, analysis and synthesis, and will be represented by means of Tables and Graphs, the results of the Legal Research. After obtaining these research results, we will determine the conclusions and recommendations of the study.